Do the effects of cannabis on the hippocampus and striatum increase risk for psychosis?. (May 2020) - Daniju, Y.; Bossong, M.G.; Brandt, K.; Allen, P.
Highlights: Cannabis is thought to increase the risk for psychosis and psychotic like experiences. We use a preclinical model of psychosis, the MAM model, as a framework to examine if psychosis risk in cannabis users is mediated by the effects of cannabis on the hippocampus. Cannabis use can affect hippocampal function and structure but the evidence that cannabis increases striatal dopamine function is less robust. Multimodal neuroimaging approaches are needed to better test the prediction of the MAM model in relation to cannabis use/administration. Abstract: Cannabis use is associated with increased risk of psychotic symptoms and in a small number of cases it can lead to psychoses. This review examines the neurobiological mechanisms that mediate the link between cannabis use and psychosis risk. We use an established preclinical model of psychosis, the methylazoxymethanol acetate (MAM) rodent model, as a framework to examine if psychosis risk in some cannabis users is mediated by the effects of cannabis on the hippocampus, and this region's role in the regulation of mesolimbic dopamine. We also examine how cannabis affects excitatory neurotransmission known to regulate hippocampal neural activity and output. Whilst there is clear evidence that cannabis/cannabinoids can affect hippocampal and medial temporal lobe function and structure, the evidence that cannabis/cannabinoids increase striatal dopamine function is less robust. There is limited evidence that cannabis use affects cortical and striatal glutamate levels, but there are currently too few studies to draw firm conclusions. Future work is needed to test the MAM model in relation to cannabis using multimodal neuroimaging approaches.